Effect of erosion void on segmental tunnel lining: 2D numerical investigation. (July 2022) - Qin, Xiaogang; Zhang, Guozhu; Ge, Ruoyu
Abstract: The effects of erosion voids on the performance and safety of linings and longitudinal joints in the transverse tunnel section are investigated using the plane strain finite element method in this study. Erosion voids located at the shoulder, springline, haunch, and invert of the tunnel are considered. First, the effectiveness of the numerical model is examined by comparing the internal forces under full contact conditions against the results from previous studies. Then, a parametric study is conducted to investigate the effect of erosion voids on the internal forces of longitudinal joints and tunnel deformations in the transverse section. The sensitivities of burial depth, earth pressure coefficient, and rotation stiffness ratio of longitudinal joints on the response of segmental linings under the presence of erosion voids are also analyzed. The results show that erosion voids at the shoulder and springline of the tunnel can intensify the ovalisation of the tunnel, whereas the voids at haunch and invert can lead to remarkable settlement of the lining circle. Finally, the opening and deterioration of structural integrity of the longitudinal joints are assessed, and a simplified method for the evaluation of joint safety is introduced, which can provide insight into how the joint integrity is jeopardized under the presence of erosion voids.